Advances in ablative treatment for human papillomavirus related cervical pre-cancer lesions - Lili Xu; Yanming Jiang; Renfeng Zhao (BMJ Publishing Group, 2023)
HPV infection is the primary cause of cervical intraepithelial neoplasia (CIN), with persistent high-risk HPV infection being the leading factor in the development of cervical cancer. In addition to the application of large loop excision of the transformation zone (LLETZ) for the treatment of cervical pre-cancerous lesions, various ablative techniques, including thermal ablation, cryotherapy, carbon dioxide (CO2) laser therapy, and focused ultrasound therapy also play significant roles in the management of cervical intraepithelial neoplasia. This review presents a comprehensive overview of the pathophysiology of cervical HPV infection and discusses the ablative methods commonly used in clinical practice, along with their indication and contradiction, especially in women with high-grade squamous intraepithelial lesions. The aim is to identify safe and effective treatment strategies for treating cervical intraepithelial neoplasia, thereby avoiding under- or over-treatment, which may reduce the incidence and progression of cervical cancer through timely diagnosis and treatment.